Aktivitas Antifungi Ekstrak Metanol Bunga Kamboja Putih (Plumeria acuminata) Terhadap Aspergillus clavatus - Berty Oktavia (Jurnal Labora Medika, 2017)
Aspergillus clavatus is able to produce mycotoxin compound that cause pathology in animals and humans. The growth of A. clavatus can be inhibited by using methanol extract of Plumeria acuminata Ait. since P. acuminata has an ability to produce natural antifungal. This study aims to investigate the concentrate of methanol extract in P. acuminata which can be utilized to inhibit the growth of specific mushroom, particularly A. clavatus AMB1. This experiment is conducted for three months, January to March 2017 in Microbiology Laboratory of Mathematics and Natural Sciences of Tanjungpura University Pontianak and in Laboratory of Plantation Product Processing of State Polytechnic Pontianak. This study employed Completely Randomized Design (CRD) with 7 treatments, specifically negative control (0 g/ml), solvent control (tween 80), positif control (ketoconazole 0,02 g/ml) and concentrate of P. acuminata (0,6 g/ml, 0,7 g/ml, 0,8 g/ml, 0,9 g/ml). The findings indicate that the lowest concentrate of extract, particularly 0,6 g/ml has 57,6% ability to inhibit the growth of A. clavatus AMB1 and strong level of antifungal activity. Extract concentrate of 0,9 g/ml is the highest extract concentrate that has similar antifungal activity to 0,02 g/ml  antifungal ketoconazole and extremely strong level of antifungal activity.